(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Over the last ten years, the popularity of homeschooling has skyrocketed. This group includes brilliant and talented kids, yet despite this expansion, the research literature has not increased much. Investigators questioned 13 parents of talented homeschooled children to get a better understanding of the smart homeschooling family. The data revealed four main themes: (a) parents are the experts, (b) isolation, (c) difficulties, and (d) intimate roles. These parents only chose to homeschool after repeated efforts to collaborate with the public school, and the women held the main responsibility for homeschooling in these households, according to the findings. Though the transition to homeschooling eased many of the problems that these families had in public school, it also presented a new set of obstacles. This exploratory research aims to learn more about why parents of talented children choose to homeschool their children.